Pregnancy Predictors after Intrauterine Insemination in Cases of Unexplained Infertility: A Prospective Study. (21st September 2016) - Ganguly, Ishita; Singh, Aparna; Bhandari, Shilpa; Agrawal, Pallavi; Gupta, Nitika
Abstract : Introduction . Aim of the study was to find the effect of various prognostic factors in cases of unexplained infertility undergoing controlled ovarian stimulation (COS) with intrauterine insemination (IUI). Methods . 146 cases of unexplained infertility were included. A maximum of 3 cycles of IUI were done with clomiphene citrate/HMG. Ovulation trigger was given when the largest follicle diameter was >18 mm, and IUI was planned 36 hours later. Luteal phase support was given for 15 days, urine pregnancy test was done on day 15, ultrasonography was done at 7 weeks, and pregnancy was followed up till delivery. Results . A total of 146 couples have undergone 239 cycles of IUI out of which 27 had UPT positive after 15 days. 14.8% had 1st-trimester abortion while 3.7% were ectopic. 86.3% were singleton pregnancies and 13.6% were twins. CPR was 11.29% per cycle and 18.4% per couple; LBR was 9.2% per cycle. Apart from duration of stimulation (p = 0.037 ) and number of treatment cycles (p = 0.045 ), no other factors had significant prognostic value. Conclusion . For unexplained infertility, IUI can be done to provide patients with the time that they need before moving on to IVF while providing a respectable chance of pregnancy.